Analysis of maturity in use of the information technology in a sustainable management of transport logistics, according to the perception of specialists - Aquino da Silva, Fabio; Vieira Barboza, Douglas; Meirelles Drumond, Geisa; Jasmim Meiriño, Marcelo; Picinini Méxas, Mirian (Perspectivas Contemporâneas, 2022)
The management of transport logistics in industries is a good opportunity to implement sustainable organizational management practices. All over the world, the great concentration of cargo transport by land modal raises the cost of sustainable management of transport logistics, favoring the development of models about the impact of Information Technology (IT) use. This article aims to analyze the perception of transport specialists regarding the degree of contribution of information technologies in the more sustainable management of transport logistics in industries from a sampling of transport logistics in a beverage industry operating in the American continent. The research methodology involved a case study with a focus group, addressing the relationship between information technology and sustainability. Within the same transport operation, benchmarking the effects of sustainable performance with the use of IT capability are also analysed. The results of the study indicate that, for the Southern region of the American Continent, existing technologies when used in the transport operation have a greater degree of contribution to sustainable management.